The adoption of information systems innovation: study of a learning support system and its adoption in the medical education field. (1st January 2013) - Perez, Gilberto
This study analysed the main factors influencing information systems (ISs) adoption in the medical education sector. We will also evaluate the results of the adoption of one such innovation: e-Class, an information system used as a teaching aid by faculty of the Santa Casa de São Paulo School of Medical Sciences. We conducted a survey of faculty members in the School's undergraduate programmes in medicine, nursing, and speech-language pathology and audiology. Data were collected by means of a questionnaire and subsequently treated through multiple linear regression analysis and structural equation modelling. Our results suggest that adoption of e-Class is influenced by the perceived characteristics of innovation (PCI), and influences the perception of new possibilities for innovation in the medical education field. Of several PCIs studied, those that stood out most markedly were result demonstrability and relative advantage.